Developing managerial skills in engineers and scientists : - Badawy, M. K. (Van Nostrand Reinhold, 1995)
Developing Managerial Skills in Engineers and Scientists Second Edition Michael K. Badawy If you’re an engineer or scientist who has suddenly been thrust into the world of management, you may find yourself thinking that managing people is more of a challenge than your former highly technical job. Veteran management consultant Michael K. Badawy couldn’t agree more. He says, "The primary problems of engineering and R&D management are not technical—they are human." Badawy offers real help for the human side of technical management in his classic Developing Managerial Skills in Engineers and Scientists. Since 1982, thousands of technical executives, supervisors, managers, and students have turned to this classic for hands-on management techniques.